Sequencing alignment analysis - li lei (22680179) (2025)
Sequencing alignment analysis of EPHB4, LITAF, SLC12A4, TM9SF4 in PK15 cells, PK15ΔEPHB4+/-，PK15ΔLITAF+/-，PK15ΔSLC12A4+/-，PK15ΔTM9SF4+/-，PK15-TM9SF4-KO